Clinical management of Australian adolescents and young adults with acute lymphoblastic and myeloid leukemias: A national population‐based study. Issue 11 (24th July 2018) - White, V. M.; Skaczkowski, G.; Pinkerton, R.; Coory, M.; Osborn, M.; Bibby, H.; Nicholls, W.; Orme, L. M.; Conyers, R.; Phillips, M. B.; Harrup, R.; Walker, R.; et al.
Abstract: Background: While several studies have examined the treatment of adolescents and young adults (AYAs) with acute lymphoblastic leukemia (ALL), studies of acute myeloid leukemia (AML) are rare. Using national data for Australia, we describe (i) the number and type of treatment centers caring for AYAs, (ii) induction/first‐line treatments, and (iii) survival outcomes. Procedure: National population‐based study assessing treatment of 15‐ to 24‐year‐olds diagnosed with ALL or AML between 2007 and 2012. Treatment details were abstracted from hospital medical records. Treatment centers were classified as pediatric or adult (adult AYA‐focused or other adult; and by AYA volume [high/low]). Cox proportional hazard regression analyses examined associations between treatment and overall, event‐free, and relapse‐free survival outcomes. Results: Forty‐seven hospitals delivered induction therapy to 351 patients (181 ALL and 170 AML), with 74 (21%) treated at pediatric centers; 70% of hospitals treated less than two AYA leukemia patients per year. Regardless of treatment center, 82% of ALL patients were on pediatric protocols. For AML, pediatric protocols were not used in adult centers, with adult centers using a non‐COG 7+3‐type induction protocol (51%, where COG is Cooperative Oncology Group) or an ICE‐type protocol (39%, where ICE is idarubicin, cytarabine, etoposide). Exploratory analyses suggested that for both ALL and AML, AYAs selected for adult protocols have worse overall, event‐free, and relapse‐free survival outcomes. Conclusions: Pediatric protocols were commonly used for ALL patients regardless of where they are treated, indicating rapid assimilation of recent evidence by Australian hematologists. For AML, pediatric protocols were only used at pediatric centers. Further investigation is warranted to determine the optimal treatment approach for AYA AML patients.